Strategies for Potential Participation of Women in Sericulture: Issues and Options - S. Lakshmanan,; R.G.Geetha Devi, (Journal of Agricultural Extension Management, 2025)
In India, more than 65 per cent of rural people depend on agriculture for their livelihood. The rate of dependence on agriculture has not declined even after Economic Liberalization initiated in 1991. It is now recognized that poor employment generation has been a major casualty of the Indian neo-liberal economic reform process. The major loser in the economic liberation process is the resource poor farmer and gender, as they do not have direct access to benefits from the economic gain attained through the economic reform process. There has been a perceptible increase in participation of women in agriculture due to rise in seasonal demand for labour for operations traditionally performed by women, and due to increase in employment of men in non-agricultural activities. Women play a key role in crop husbandry, sericulture, fisheries, forestry and post harvest technology and have diverse responsibilities as head of farm household, farm manager, member of family work force and income generator. However research, extension and training agencies have often neglected women's productive role. Women's participation needs to be acknowledged and incorporated in planning agricultural development. Although agriculture has failed in economic and social empowerment of women to a great extent, there are sectors like sericulture, where women play an important role in decision-making and higher participation